Problems in the Kitabah Learning Process at Ash-Sholihin IT Middle School, Medan City - M. Dzaki Sholihin; Nabila Arrahma; Lolita Sari Siregar; Marhamah Salwa; Sahkholid Nasution (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
This study aims to identify the issues encountered in the process of kitabah (writing) learning at SMP IT Ash-Sholihin. Arabic language education in Indonesia began with the spread of Islam in the 13th century, and one of the main objectives of teaching this language is to develop students' abilities to use Arabic, both orally and in writing. However, this process is full of challenges and is not straightforward. This research identifies various problems that arise in kitabah learning, such as difficulties in understanding Arabic grammar, vocabulary, and sentence structures. Additionally, the lack of adequate media and learning resources is a significant barrier. This study employs a qualitative method with a case study approach at SMP IT Ash-Sholihin. The results indicate that there is a need for improvements in teaching methods and the provision of better facilities and learning resources to support the kitabah learning process. Consequently, it is hoped that students' Arabic writing skills can be significantly improved.